Knowing Dental Students' Discourses on Situational Planning in Integrated Clinic: A Qualitative Study - François Isnaldo Dias Caldeira; Mariana Martins de Vitro; Ihanael Ifanger; Leandro Araújo Fernandes; Renata Ribeiro Bruzadelli; Rodrigo Alvitos; Larissa Santana Rodriguez (Association of Support to Oral Health Research (APESB), 2024)
Objective: Dentistry from the Universidade Federal de Alfenas who were enrolled in the seventh period and who took the Integrated Clinic I Discipline (ICID) in the emergency remote learning model (ERLM). Material and Methods: This is a qualitative and descriptive study. The information was collected through questionnaires applied by the Professors during the ICID. Subsequently, the professor evaluated the treatment developed in virtual form by each student regarding its logical sequence and the most appropriate treatment for each case. The results of the answers were transcribed and submitted to lexicographical textual, Descending Hierarchical Classification, and Similitude analysis in the Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires(IRAMUTEQ) program. Results: The students described the online situational treatment planning in five essential steps: adequacy of the oral environment, restorative need, prosthetic need, rehabilitation by prosthesis on the implant, and corrective orthodontic treatment. Conclusion: It was observed that the students who enrolled in ICID presented well-integrated planning during ERLM, despite the COVID-19 pandemic hindering these students' contact between theoretical teaching and the integrated practices in dentistry offered by the educational institution.